Combining science and faith for better quality and safety in halalan toyyiban products - Azmi, Nor Azrini Nadiha; Najihah Mohd Noor; Amal Elgharbawy; Noviyan Darmawan (IPB University, 2024)
Halalan Toyyiban, a concept rooted in Islamic teachings, is focused on quality, safety, ethical considerations, and permissibility.